Synergy of Physical, Mental, Financial, and Environmental Health in Support of Sustainable Development Goals (SDGS) - PASUPATI, Bayu; LAKSMI, Putu Ayu Sita (PT Keberlanjutan Strategis Indonesia, 2025)
The 2025 Community Service Program – Community Empowerment by Warmadewa University Students (KKN-PMM) in Belantih Village, Kintamani District, Bangli Regency, was held for one month with the theme